2023
DOI: 10.1021/acsami.3c05659
|View full text |Cite
|
Sign up to set email alerts
|

Nontoxic Cross-Linked Graphitic Carbon Nitride-Alginate-Based Biodegradable Transparent Films for UV and High-Energy Blue Light Shielding

Abstract: Flexible, transparent, and biodegradable films that can shield dangerous UV and high-energy blue light (HEBL) are high in demand to satisfy the ever-increasing expectations for environmental sustainability. To achieve this goal, biopolymer alginate is an excellent choice that has an outstanding film-forming ability. However, alginate has the limitation of poor UV and HEBL blocking ability. Thus, in this study, UV and HEBL blocker graphitic carbon nitride (g-C 3 N 4 ) was incorporated in alginate films to enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 65 publications
(137 reference statements)
0
5
0
Order By: Relevance
“…When 5% (w/w) GO was added, the (CMC/SA) 15 @GO 5 film effectively blocked over 94% of UVA and 100% of UVB and UVC, while the (CMC/SA) 19 @GO 5 film completely blocked UVA. This is attributed to the conjugated aromatic structure and planar 2D structure of GO, which absorb and reflect most UV radiation …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When 5% (w/w) GO was added, the (CMC/SA) 15 @GO 5 film effectively blocked over 94% of UVA and 100% of UVB and UVC, while the (CMC/SA) 19 @GO 5 film completely blocked UVA. This is attributed to the conjugated aromatic structure and planar 2D structure of GO, which absorb and reflect most UV radiation …”
Section: Resultsmentioning
confidence: 99%
“…This is attributed to the conjugated aromatic structure and planar 2D structure of GO, which absorb and reflect most UV radiation. 53 Furthermore, the thermal stability of the (CMC/SA) n @GO x films was evaluated using TGA. The findings revealed three distinct thermal degradation stages within the temperature range of 30−600 °C (Figure 5C).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In these cases, these leached nanoparticles may create secondary pollution, and some cases pose health risk to the aquatic environment. 340,345 For this reason, during selection, the nanoparticle leaching rate and their cytotoxicity effect on the local environment should be carefully analyzed. A recent study showed that introducing a polishing step before membrane (nanoparticle incorporated) application for water reclamation can remove potentially leached nanoparticles.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Within the solar spectrum, UV radiation spans a wavelength range of 200−400 nm, further categorized into UV−A (320−400 nm, known as blacklight UV), UV−B (280−320 nm, associated with health hazards), and UV−C (200−280 nm, with germicidal properties). 1 UV radiation is notorious for its ability to cause photodegradation in polymers by activating the chromophores. 2 In this context, there is considerable attention directed toward UV protective materials, especially in the development of optically transparent and UV-shielding polymeric composites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Ultraviolet (UV) light is renowned for its adverse impact on human health and its capacity to induce the photodegradation of organic materials. Within the solar spectrum, UV radiation spans a wavelength range of 200–400 nm, further categorized into UV–A (320–400 nm, known as blacklight UV), UV–B (280–320 nm, associated with health hazards), and UV–C (200–280 nm, with germicidal properties) . UV radiation is notorious for its ability to cause photodegradation in polymers by activating the chromophores .…”
Section: Introductionmentioning
confidence: 99%